Identity Styles and Delay of Gratification among Omani Students - Alzubaidi , Abdulqawi; Al-Balushi, Basma (Jordan Journal of Educational Sciences, 2015)
The aim of the study is to explore identity processing styles and delay of gratification and whether academic delay can be predicted from identity styles , gender and level of education among 11th and 12th grade pupils and university students in Oman The sample included 495 (331 from grades 11 and 12 and 164 SQU students) who completed the identity style orientation scale by Berzonsky measuring four dimensions (informational, normative, avoidance and diffuse) and the delay of gratification scale. The validity and reliability of both scales were obtained. Findings show that the mean responses for the sample in diffuse identity was high, and the mean responses for the other three identities were average, whereas the mean for the delay of gratification was high. There were significant effect for the level of education (grade 11 and 12 vs. university), but no effect was observed for gender. In addition, the results show that delay of gratification can be predicted from five demographical variables including diffuse, normative, avoidance identities (negative correlation), gender (negative correlation), informational identity. Moreover, while the students at grade 11 and 12 can be predicted from three identity styles (normative, avoidance (negative correlation) and informative, the university students can be predicted from only one variable which is diffuse identity. On the basis of the results, several recommendation and proposals were presented